ANALISIS KINERJA KEUANGAN DENGAN METODE EVA DAN MVA PADA PT.PP LONDON SUMATRA INDONESIA Tbk - shela puspita; Eri Bestary Al Haitamy; Pramesti Nurul Adinda (Journal of Applied Accounting And Business, 2025)
This study aims to analyze the financial performance of PT.PP London Sumatra Indonesia Tbk (LSIP), during the 2019-2023 period. The method used in this research is the calculation method of Economic Value Added (EVA) and Market Value Added (MVA). The type of data used is secondary data or financial information derived from the LSIP Annual Financial Report. The data collection method used is the documentation technique in the form of collecting written data in documents through the Indonesia Stock Exchange (IDX) website and the official website of PT.PP London Sumatra Indonesia Tbk. The results showed that in the 2019-2023 research period, the analysis of financial performance using the EVA and MVA methods was overall positive, which means that the company's financial performance is healthy so that the company is able to generate accounting profit, economic profit and generate wealth value for investors.